2022
DOI: 10.1590/1806-9282.20220222
|View full text |Cite
|
Sign up to set email alerts
|

Extended-spectrum beta-lactamases among Klebsiella pneumoniae from Iraqi patients with community-acquired pneumonia

Abstract: OBJECTIVE: Beta-lactams resistance is a major clinical problem in treating pneumonia. This study aimed to detect the extended-spectrum betalactamases (ESBL) genes in Klebsiella pneumoniae among patients with community-acquired pneumonia (CAP) in Al-Najaf City, Iraq. METHODS: A total of 511 sputum samples were obtained from all suspected patients with CAP in Al-Najaf City, Iraq, from March 2020 to September 2020. Sputum samples were subjected to microbiological tests. The disk diffusion method was used to test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…In another study by Banerjee et al (2021) from India, all CR-hvKp ( n = 9) harbored bla SHV and bla CTX–M , whereas bla TEM was not detected. In this study, the bla CTX–M was the most frequent ESBL among carbapenem-resistant K. pneumoniae isolates that was in line with the previous report from Iraq ( Raouf et al, 2022 ). In the last decade, bla TEM and bla SHV variants have become less dominant than bla CTX–M , despite being the most universal ESBLs ( Soltani et al, 2020 ; Raouf et al, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In another study by Banerjee et al (2021) from India, all CR-hvKp ( n = 9) harbored bla SHV and bla CTX–M , whereas bla TEM was not detected. In this study, the bla CTX–M was the most frequent ESBL among carbapenem-resistant K. pneumoniae isolates that was in line with the previous report from Iraq ( Raouf et al, 2022 ). In the last decade, bla TEM and bla SHV variants have become less dominant than bla CTX–M , despite being the most universal ESBLs ( Soltani et al, 2020 ; Raouf et al, 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the bla CTX–M was the most frequent ESBL among carbapenem-resistant K. pneumoniae isolates that was in line with the previous report from Iraq ( Raouf et al, 2022 ). In the last decade, bla TEM and bla SHV variants have become less dominant than bla CTX–M , despite being the most universal ESBLs ( Soltani et al, 2020 ; Raouf et al, 2022 ). Antibiotic use plans differ in each region, which may cause selection pressure for the circulation of ESBL-producing isolates and explain these inconsistencies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In recent years, K. pneumoniae has emerged as a significant nosocomial and opportunistic pathogen. Antibiotic resistance, with the production of extended-spectrum β-lactamases (ESBL), carbapenemases or aminoglycosides resistance, is common in K. pneumoniae ( Raouf et al., 2022 ; Jwair et al., 2023 ; Khoshnood et al., 2023 ), which brings big challenges to the therapy of infection of K. pneumoniae . The emergence of carbapenem-resistant hypervirulent K. pneumoniae (CR-hvKP) has exhibited prevalence since 2010 ( Lan et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies are conducted by researchers in Iraq, such as obtaining 61 Klebsiella isolates (33.88%) from a total of 180 samples collected from two clinical sources in Baghdad province [17 In a local study by Hasan et al, [18] discovered that out of a total of 207 Gram-negative bacteria isolates, K. pneumoniae was the second most prevalent with a prevalence rate of 35.74 %; based on gender, 47 (63.51%) of the K. pneumoniae isolates were females and 27 (36.49%) were males. In a local study by Raouf et al, [19] who found out of a total of 308/511 (60.3%) Gram-negative bacteria isolates, K. pneumoniae was prevalent with the percentage of 163/511 (31.9%), from other hand depending on the gender the K. pneumoniae isolates were 61 (37.4%) females and 102 (62.6%) males.…”
Section: Dna Extraction and Pcr Assaymentioning
confidence: 95%